Physical quality of broiler chickens fed diets containing fish oil and different levels of purslane meal. (October 2019) - Kartikasari, L R; Hertanto, B S; Sutanto, S Y; Nuhriawangsa, A M P
Abstract: The aim of the study was to investigate the effect of dietary supplementation of purslane meal (Portulaca oleraceae) and sardines fish oil as a source of omega-3 fats on physical quality of broiler chickens. A total of 180 one-day old unsexed Cobb broiler chickens were used in this study. Chickens were randomly placed into 30 pens with each pen consisted of 6 birds. The pens were randomly assigned to five dietary treatments with 6 replicates (36 birds per treatment). The diets were prepared from a basal diet (P0). The experimental diets were formulated by adding the basal diet containing 1.5% sardines fish oil and levels of purslane meal 0 (P1), 6 (P2), 12 (P3), and 18% (P4). Water and diets were provided ad libitum for a period of 35 days. Six chickens for each treatment were processed as carcass and breast meat (Pectoralis Major) samples were collected for physical quality analysis. The data were analysed using analysis of variance (ANOVA). Differences between treatment means were further analysed using Duncan's New Multiple Range Test. Results showed that the results showed that adding Portulaca oleracea (purslane) meal into the diets at a level of 12 and 18% did not influenced pH value. Feeding diets enriched with purslane meal up to a level of 18% for 35 days did not alter meat WHC with the average of approximately 51%. Diets containing purslane meal decreased meat cooking loss. Meat tenderness of chickens fed diets supplemented with 12% purslane meal (1.12) was higher than those fed 18% purslane meal (1.93). It was concluded that dietary levels of purslane meal up to a level of 12% did not affect the physical quality of broiler chickens.